Correlation between canopy density using NDVI and invasive species diversity in Gunung Dahu Research Forest - Elsa Widyastuti; Istomo; Rachmat, Henti Hendalastuti (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2024)
Gunung Dahu Research Forest is a forest area dominated by meranti species. The presence of human activity in forest areas has the potential to bring in invasive species. The presence of invasive plant species can have negative impacts on the ecosystem. This research aims to estimate canopy density in the Gunung Dahu Research Forest using the Normalized Difference Vegetation Index and its relationship with the diversity of invasive understory species to produce appropriate management recommendations. The canopy density class map was made using a desk study and the understorey data was taken using vegetation analysis. Correlation and regression tests were conducted to determine the relationship between NDVI values ​​and other variables. Based on the results of the NDVI analysis, three canopy density classes were obtained, low, medium, and high. The low canopy density class has the highest number of invasive species, while the high canopy density class has the least number of invasive plant species. The Poaceae family is the most found family with D. setigera as the dominant invasive species. There is a strong correlation between canopy density and NDVI values. Keywords: Dipterocarpaceae, Shorea sp., Poaceae